USE OF CAPSULE ENDOSCOPY TO EVALUATE THE EFFECTS OF MELOXICAM AND DICLOFENAC ON THE SMALL BOWEL MUCOSA IN PATIENTS WITH ANKYLOSING SPONDYLITIS: THE FIRST EXPERIENCE - A E Karateev; A G Bochkova; O A Rumyantseva; E Yu Tyukhova; E L Nasonov (Научно-практическая ревматология, 2011)
Small bowel (SB) injury is a common complication from the use of nonsteroidal anti-inflammatory drugs (NSAIDs). According to clinical trials, selective cyclooxygenase-2 inhibitors are safer in this respect. Meloxicam belongs to selective NSAIDs; however, its effect on the SB has been inadequately investigated. Objective: to compare the effects of meloxicam 15 mg/day and diclofenac 150 mg/day on the SB mucosa. Subjects and methods. A study group comprised 15 patients, including 6 men and 9 women (mean age 42.3+17.1 years), with ankylosing spondylarthritis (AS); 7 of them took meloxicam 15 mg/day for at least one month and 8 had diclofenac 100-150 mg/day. The SB was evaluated from capsule endocopy (CE) readings. Results. SB erosions (n = 3 to 20 or more) were found in 11 patients: 5 (71.3%) and 6 (75.0%) subjects taking meloxicam and diclofenac, respectively (p = 0.82). The average amount of erosions in those receiving meloxicam (6.2+4.7) was less than in those having diclofenac (9.4+7.3; p = 0.13). One patient taking diclofenac was suspected of having Crohn's disease shown by CE and then confirmed by colonoscopy. Conclusion. Meloxicam has demonstrated a less negative effect than diclofenac on SB, although this difference was statistically insignificant. Small and bowel pathology frequently occurs in patients with AS and may be associated not only with the negative effect of the drugs, but also with comorbid inflammatory bowel diseases. There is a need for further studies of the distal gastrointestinal tract and for those of the effect of NSAIDs on the SB.